PURSUIT OF INCLUSIVE EDUCATION: INCLUSION OF TEACHERS IN INCLUSIVE EDUCATION - Baranauskienė, Ingrida; Saveikienė, Diana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
By focusing on teachers’ approach, the article analyses one of the most relevant issues of today’s realities of education – the inclusive education. The following is an important task for politicians for education, school leaders, teachers and greatly affects and influences the life of families with children with disabilities. Object of the research: inclusion of teachers in inclusive education. Aim of the research: to examine aspects of teachers’ inclusion in inclusive education by implementing the statistical analysis according to The Teachers’ Attitudes Toward Inclusion Scale (TATIS) survey (Gregory, Noto, Cullen, 2010). This study adopted a descriptive survey research design, with 105 teachers as participants from selected secondary schools in Klaipėda city and Klaipėda district, Lithuania. Research results: A study has been conducted demonstrating that the attitudes of educators participating in the study to inclusive education of pupils with a disability are basically positive. The analysis of the research data received allow the teachers are not sufficiently prepared to provide assistance to their students with orientation towards the inclusive training tasks. Teachers who participated in the study agree that all school classes should be rebuilt to meet the needs of students with disabilities and that students with disabilities should be taught in a general education school in an equal educational environment with peers without disabilities. The differences between teachers' attitudes to the inclusive education model and the type of pedagogical school were statistically significant. More than just a gymnasium teacher, either a progymnist or a primary school teacher, fully agrees that the model of inclusive education ensures a more effective transition of pupils with disabilities from special education to general education schools.